Employee Perceptions of Job Demands, Autonomy, and Organizational Support: A Study on Workplace Stress and Satisfaction - Maharjan, Shreejana (NPRC Journal of Multidisciplinary Research, 2024)
Background: Employee well-being has become a key determinant of organizational performance, with demands, autonomy, and support identified as major contributors to workplace satisfaction and mental health. Objective: The study aims to investigate the extent to which employees perceive their work as demanding, requiring significant skills, and allowing autonomy, as well as how these factors impact feelings of favoritism, stress, and workplace support, including health benefits and training. Methods: Data were collected through a structured survey administered to 89 respondents, utilizing Likert-scale questions to assess opinions on job demands, autonomy, favoritism, stress levels, information sufficiency, and consistency in job roles. Descriptive statistics, primarily frequency and percentage distributions, were employed to analyze participant responses. Findings: The results indicate a mixed response to job demands, with a notable portion of employees agreeing that their work is effort-intensive and skill-demanding. Despite these demands, only moderate levels of autonomy were reported, as many participants indicated limited choice in determining their work processes. Favoritism and bullying perceptions were low overall, but stress was reported to impact performance for a considerable segment of employees. Health and training support appeared somewhat limited, with only a portion of employees confirming regular access to these resources. Conclusion: Findings suggest a critical need for organizations to balance job demands with adequate autonomy and support, as these factors significantly affect employee well-being and productivity. Novelty: This study uniquely combines various workplace dimensions—demands, autonomy, favoritism, stress, and support structures—into a single analysis, providing a holistic view of factors influencing employee satisfaction and stress.